Evaluation of an external foam column for in situ product removal in aerated surfactin production processes - Treinen, Chantal; Claassen, Linda; Hoffmann, Mareen; Lilge, Lars; Henkel, Marius; Hausmann, Rudolf (Frontiers in Bioengineering and Biotechnology, 2023)
In Bacillus fermentation processes, severe foam formation may occur in aerated bioreactor systems caused by surface-active lipopeptides. Although they represent interesting compounds for industrial biotechnology, their property of foaming excessively during aeration may pose challenges for bioproduction. One option to turn this obstacle into an advantage is to apply foam fractionation and thus realize in-situ product removal as an initial downstream step. Here we present and evaluate a method for integrated foam fractionation. A special feature of this setup is the external foam column that operates separately in terms of e.g. aeration rates from the bioreactor system and allows recycling of cells and media. This provides additional control points in contrast to an internal foam column or a foam trap. To demonstrate the applicability of this method, the foam column was exemplarily operated during an aerated batch process using the surfactin-producing B. subtilis strain JABs24. It was also investigated how the presence of lipopeptides and bacterial cells affected functionality. As expected, the major foam formation resulted in fermentation difficulties during aerated processes, partially resulting in reactor overflow. However, an overall robust performance of the foam fractionation could be demonstrated. A maximum surfactin concentration of 7.7 g/L in the foamate and enrichments of up to 4-fold were achieved. It was further observed that high lipopeptide enrichments were associated with low sampling flow rates of the foamate. This relation could be influenced by changing the operating parameters of the foam column. With the methodology presented here, an enrichment of biosurfactants with simultaneous retention of the production cells was possible. Since both process aeration and foam fractionation can be individually controlled and designed, this method offers the prospect of being transferred beyond aerated batch processes.